THE PROBLEM OF VIOLATING THE DISCIPLINE OF MONKS IN THE CASE OF DRUG ADDICTION COMPARE THAT TOCRIMINAL SEXUAL CONDUCT - แครบทรี, ณัฎฐปีญา; Buabkhom, Apichart; Luangrattanacharoen, Pitchaya Luangrattanacharoen (Journal of MCU Phetchaburi Review, 2024)
Research on “The problem of violating the Vinaya concerning the case of drug use by monks is compared to criminal sexual conduct. The objective is to study the concepts, meanings, patterns, and characteristics in the behavior of monks violating the disciplinary code in the case of drug addiction, and the problematic nature of the law in criminal sexual conduct. and methods for analyzing and recommending solutions to the problem of violating the discipline. The researcher determines the method for conducting the comparative study. This research is Monks are people who in Buddhism are considered to be disciples who carry on the duty of passing on Buddhism. Therefore, monks are in a high position worthy of worship and must conduct themselves in the Dhamma and Vinaya. To be a role model for the general public The fact that a monk must commit an offense (Sikkha Chapter 1 ) or violate the act of indulging in drugs must therefore be held to be violating the Dhamma law along with the worldly law. (Civil Law, Criminal Law),In order to protect Buddhism along with peace and order and good morals of society, at present (b) it is found that the punishment for monks who commit parashikkha offenses (Sikkha Chapter 1) is not yet accepted. As can be seen from Section 276, legal ethics focuses on Protecting individual freedom requires forced sexual intercourse without consent. If the victim To consent is to sacrifice legal morality.When the legal morality is sacrificed, the perpetrator is not guilty of rape under Section 276.